The Essential Role of Moisturizer in Dermatology - Shane, Franklin (Scientific Journal of Dermatology and Venereology, 2023)
Moisturizer has an important role in maintaining healthy skin. Healthy skin has sufficient moisture and is maintained, so it can function properly as a protector and barrier against harmful outside agents, such as pollution and infection. This literature review aimed to describe the role of a moisturizer in maintaining healthy skin. Moisturizer helps keep the skin moist so that the skin does not become dry and irritated. Skin that is too dry can damage the skin easily and lead to skin problems such as eczema or psoriasis. Moisturizers containing antioxidants can help protect the skin from free radical damage and prevent premature aging. Antioxidants like vitamins C and E can help prevent wrinkles, fine lines, and dark spots on the skin.